If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + (-4) = 0 6y + -4 = 0 Reorder the terms: -4 + 6y = 0 Solving -4 + 6y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 6y = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 6y = 0 + 4 6y = 0 + 4 Combine like terms: 0 + 4 = 4 6y = 4 Divide each side by '6'. y = 0.6666666667 Simplifying y = 0.6666666667
| -2x=5x-9x+16-10 | | 7=.75*20+4 | | -3/4*8 | | 3+66x=33x+22 | | -x/4=-22 | | 4(7x+1)=312 | | .6h=1.8 | | 2(3y-6)= | | 8x+3y=101 | | -4(8+5x)=-32 | | 14=4a+2 | | 5x+11=7-2x | | -94=-2(5m+7) | | -2(7x-5)+3=-14x+13 | | p/7=6.8.k/4=2 | | 3x+11=12+8x | | 193=-x+96 | | -9x-13=50 | | 60x-3x^/3x | | 7(2x+2)=-84 | | 6x-8=6(x-5) | | 23=8*1+y | | 6460-h=4181 | | 1/4=b=3.4 | | 4.6d=26.68 | | 16x-6x=56 | | 10x+7=3x+15 | | 2/3(6x-12)=-16 | | 2/3(6x-12)=- | | 440=(11)(x)(x-3) | | 92.99=x+.89 | | X+5=4.3 |